2009
DOI: 10.1021/bi802373d
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of RNA Aptamers Derived from a Genomic Human Library against the TAR RNA Element of HIV-1

Abstract: The transactivating responsive (TAR) element is a RNA hairpin located in the 5' untranslated region of HIV-1 mRNA. It is essential for full-length transcription of the retroviral genome and therefore for HIV-1 replication. Hairpin aptamers that generate highly stable and specific complexes with TAR were previously identified, thus decreasing the level of TAR-dependent expression in cultured cells [Kolb, G., et al. (2006) RNA Biol. 3, 150-156]. We performed genomic SELEX against TAR using a human RNA library to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Analysis of 64 variants of LNA/2′-O-Me modified aptamers had shown that the combination of these modifications results in higher binding affinity as compared with the unmodified RNA aptamer (Di Primo et al, 2007). To obtain genomic RNA aptamers that might reflect natural interactions of the TAR fragment with human RNA transcripts, a genomic SELEX was conducted, taking in vitro transcripts of full human genome as a starting library (Watrin et al, 2009). The hairpin-forming aptamers obtained during this process possessed high affinity to their targets ( K d from 4 to 297 nM).…”
Section: Antiviral Aptamersmentioning
confidence: 99%
“…Analysis of 64 variants of LNA/2′-O-Me modified aptamers had shown that the combination of these modifications results in higher binding affinity as compared with the unmodified RNA aptamer (Di Primo et al, 2007). To obtain genomic RNA aptamers that might reflect natural interactions of the TAR fragment with human RNA transcripts, a genomic SELEX was conducted, taking in vitro transcripts of full human genome as a starting library (Watrin et al, 2009). The hairpin-forming aptamers obtained during this process possessed high affinity to their targets ( K d from 4 to 297 nM).…”
Section: Antiviral Aptamersmentioning
confidence: 99%
“…The lower nanomolar dissociation constant (K D = 30 nM at 3 mM magnesium) of the selected RNA aptamers was attributed to closing of the aptamer loop by the consensus G and A residues [87]. Moreover, anti-TAR RNA aptamers were isolated from a genomic human library [88]. Theoretically, a genomic SELEX library contains all cellular RNA transcripts that can identify putative functional interactions involving RNA motifs [154].…”
Section: Aptamers As Antiviral Therapeuticsmentioning
confidence: 99%
“…In the case of TAR aptamers, one of the selected aptamers, (a1), formed a complex with TAR through a kissing interaction and had ~4-fold lower dissociation constant than that of a previously identified aptamer, R06 (K D : 4 nM vs . 17 nM) [88]. …”
Section: Aptamers As Antiviral Therapeuticsmentioning
confidence: 99%
“…(104) Such a kissing aptamer targeted to the trans-activating responsive (TAR) element of HIV-1 displayed both high affinity and exquisite specificity (5). RNA aptamers produced in situ in HeLaP4 cells from an expression vector inhibit TAR-dependent expression of a reporter gene.…”
Section: Rna Nanoparticles In Therapeuticsmentioning
confidence: 99%